Local Governance Policies and Advocacy Has High Impact on Waste Management Technology Transfer - Thiruchelvam, Vinesh (European Journal of Sustainable Development, 2017)
Waste management has been a challenge for developing cities of 3rd world nations. An enduring national resolve is already in place in many Governments to ensure waste management infrastructure is place as population numbers rise for major cities. Developed nations have faced the obstacles and are ready from experiences learnt to venture un-chartered path of globalization, market liberalization and sustaining industry competitiveness. This is specific for the new group of developed nations the likes of Malaysia, India, Turkey and Taiwan. Having gained all the technological growth it would be prudent for these nations to now become technology exporters in the new era. An impact initiation to this can be set for the Waste Management sector. The application of this can be adopted by any developing nation moving on towards being an exporter of knowledge and technology transfer. Keywords: Technology Transfer, Local Government Policy & Advocacy, Waste Management